1. `int te^t dt`

Integrate by parts. u = t and dv = e^t. Then du = 1 and v = e^t

`=te^t-int e^t dt`

`=te^t-e^t+c`

`=e^t(t-1)+c`

2. `int -e^(-2t)dt`

You could use substitution, but I like to just think "what would the derivative of e^-2t be? -2e^-2t. So we have half of that:

`1/2 e^(-2t)+c`

3. `int te^(t^2) dt`

Think "what would the derivative of `e^(t^2)` be? `2te^(t^2)` . Again, we just have half of that in our integral, so answer is

`1/2e^(t^2)+c`

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now